(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The presented study is the result of a laboratory testing under bending stress by collecting arms by corner butt joints with 2 staples type М1/40 of Scots pine (Pinus sylvestris L.) members and boards (OSB, PB, PW) to determine the deformation behaviour of the joints. The aim of the study is to establish the stiffness coefficients by examining the influence of the material, the reinforcement by means of a triangular wood member and the type of joints on the deformation behaviour of butt joints by staples. The results obtained could be used as a basis for future research to predict the deformation behaviour of furniture constructions as well as to find their application in the design of skeletons of upholstered furniture.